2007
DOI: 10.4049/jimmunol.178.5.2883
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Evasion of the Immune System by Converting CD4+CD25− T Cells into CD4+CD25+ T Regulatory Cells: Role of Tumor-Derived TGF-β

Abstract: CD4+CD25+ T regulatory (Treg) cells were initially described for their ability to suppress autoimmune diseases in animal models. An emerging interest is the potential role of Treg cells in cancer development and progression because they have been shown to suppress antitumor immunity. In this study, CD4+CD25− T cells cultured in conditioned medium (CM) derived from tumor cells, RENCA or TRAMP-C2, possess similar characteristics as those of naturally occurring Treg cells, including expression of Foxp3, a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
306
7
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(326 citation statements)
references
References 47 publications
8
306
7
5
Order By: Relevance
“…Therefore, our findings most likely support the evidence of peripheral conversion of CD4 + CD25 2 T cells into Foxp3 + CD4 + CD25 high T cells, occurring possibly upon exposure to TGF-b (46) and/ or chronic Ag stimulation (47). In experimental models, tumor cells have been shown to directly convert CD4 + CD25 2 T cells to Tregs through production of TGF-b, leading to tumor evasion of the immune system (48). Although CGA expression was not initially found in thymus but only in tumor cells, testis, and placenta (27), the isolation of pure thymic stromal cells of human thymus in combination with improved protocol for amplification of small RNA amounts has demonstrated that thymic epithelial cells express a highly diverse selection of genes, including many tissuespecific Ags and several CGAs such as NY-ESO-1 (49).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, our findings most likely support the evidence of peripheral conversion of CD4 + CD25 2 T cells into Foxp3 + CD4 + CD25 high T cells, occurring possibly upon exposure to TGF-b (46) and/ or chronic Ag stimulation (47). In experimental models, tumor cells have been shown to directly convert CD4 + CD25 2 T cells to Tregs through production of TGF-b, leading to tumor evasion of the immune system (48). Although CGA expression was not initially found in thymus but only in tumor cells, testis, and placenta (27), the isolation of pure thymic stromal cells of human thymus in combination with improved protocol for amplification of small RNA amounts has demonstrated that thymic epithelial cells express a highly diverse selection of genes, including many tissuespecific Ags and several CGAs such as NY-ESO-1 (49).…”
Section: Discussionsupporting
confidence: 71%
“…Some studies suggest indeed that the immunosuppressive potential of Tregs mostly derives from the conversion of conventional CD4 + T cells into iTregs in situ [55][56][57][58][59], while other reports suggest that the infiltration and local expansion of nTregs would constitute the predominant mechanism [44, 60-62]. As mentioned above, it is difficult to differentially track nTregs and iTregs in vivo because no truly populationspecific surface marker has been identified so far.…”
Section: Migration and Retention Of Tregsmentioning
confidence: 99%
“…Importantly, the neutralization of TGF-β in vivo reduces tumor burden in mice. Hence, it seems that tumors promote the differentiation of iTregs due to a milieu rich in TGF-β [56]. However TGF-β also can expand pre-existing nTregs [61].…”
Section: Migration and Retention Of Tregsmentioning
confidence: 99%
“…An important role of TGFβ in mediating Treg expansion through direct interaction of CD4 + CD25 + cells with DCs has been demonstrated in various systems [20,21]. In addition, resident tumor DCs might also actively promote immunosuppression through expansion of Tregs [22]. Induction of FoxP3 + Tregs in vivo requires direct contact of CD4 + CD25 − T cells with DCs for TCR ligation and costimulation with exogenous or endogenous TGFβ [23,24].…”
Section: Role Of Stat3 In Regulatory T Cellsmentioning
confidence: 99%